Typology of "fatigue" by heart rate variability analysis in elite Nordic-skiers - Schmitt, L.; Regnard, J.; Parmentier, A. L.; Mauny, F.; Mourot, L.; Coulmy, N.; Millet, G. P. (International Journal of Sports Medicine, 2015)
This study investigated changes in heart rate variability (HRV) in elite Nordic-skiers to characterize different types of "fatigue" in 27 men and 30 women surveyed from 2004 to 2008. R-R intervals were recorded at rest during 8 min supine (SU) followed by 7 min standing (ST). HRV parameters analysed were powers of low (LF), high (HF) frequencies, (LF+HF) (ms(2)) and heart rate (HR, bpm). In the 1063 HRV tests performed, 172 corresponded to a "fatigue" state and the first were considered for analysis. 4 types of "fatigue" (F) were identified: 1. F(HF(-)LF(-))SU_ST for 42 tests: decrease in LFSU (- 46%), HFSU (- 70%), LFST (- 43%), HFST (- 53%) and increase in HRSU (+ 15%), HRST (+ 14%). 2. F(LF(+) SULF(-) ST) for 8 tests: increase in LFSU (+ 190%) decrease in LFST (- 84%) and increase in HRST (+ 21%). 3. F(HF(-) SUHF(+) ST) for 6 tests: decrease in HFSU (- 72%) and increase in HFST (+ 501%). 4. F(HF(+) SU) for only 1 test with an increase in HFSU (+ 2161%) and decrease in HRSU (- 15%). Supine and standing HRV patterns were independently modified by "fatigue". 4 "fatigue"-shifted HRV patterns were statistically sorted according to differently paired changes in the 2 postures. This characterization might be useful for further understanding autonomic rearrangements in different "fatigue" conditions.